Chalcones: An Update on Cytotoxic and Chemoprotective Properties - Go, M.L.; Wu, X.; Liu, X.L.
Chalcone is a unique template that is associated with several biological activities. In this review, an update of the cytotoxic and chemoprotective activities of chalcones is provided. Cytotoxicity against tumour cell lines may be the result of disruption of the cell cycle, inhibition of angiogenesis, interference with p53- MDM2 interaction, mitochondrial uncoupling or induction of apoptosis. Structural requirements for cytotoxi activity vary according to the mechanisms of action. For anti-mitotic activity, the presence of methoxy substituents, a-methylation of the enone moiety and the presence of 2' oxygenated substituents are favourable features. Conformational restraint of the chalcone template generally leads to a decrease in cytotoxic activity. Chemoprotection by chalcones may be a consequence of their antioxidant properties, mediated via inhibition or induction of metabolic enzymes, by an anti-invasive effect or a reduction in nitric oxide production. Hydroxyl and prenyl substituents are associated with antioxidant properties and induction of quinone reductase activities. The thiol reactivity of chalcones is likely to contribute to both cytotoxic and chemoprotective properties of these compounds.
Keywords: CHALCONES; CYTOTOXIC; CHEMOPROTECTIVE; ORGANIC SYNTHESIS; PHYSICOCHEMICAL CHARACTERISATION